(untitled) (Journal of Misan Researches, 2023)
The research shows accurate evidence to know the authenticity of the criminal evidence obtained illegally. In addition, it supports all legal professionals, whether they are judges, criminal investigators, or researchers in the field of forensic evidence. The importance of modern forensic evidence in this field has increased with the scientific development and technology and the use of various rapid developments in modern scientific ways to try to get rid of crimes that are difficult for the old methods to detect (classical forensic evidence). In addition, the justice apparatus needs a legal and scientific basis to support criminal evidence so that it is fair in front of everyone and far from misleading, in addition to preparing an approved and unified mechanism in procedures to obtain evidence by official legal methods that respect human prestige and dignity.